2014
DOI: 10.1080/14786419.2014.964710
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic fingerprint classification of Brachychiton acerifolius organs via UPLC-qTOF-PDA-MS analysis and chemometrics

Abstract: Brachychiton acerifolius, or Sterculia acerifolia as formerly known, is a member of a genus reported for a myriad of bioactive compounds. Metabolome analysis of B. acerifolius--leaves, flowers and seeds--and quantification of its major compounds are demonstrated in this study. Metabolites were analysed via UPLC-PDA-qTOF-(±) ESI-MS and UPLC/ITMS, with a total of 56 metabolites characterised including 30 flavonoids, 2 anthocyanins, 6 phenolic acids (i.e. citric and hydroxycitric acid conjugates) and 8 fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…[5] A cursory study of the methanol extract from the Illawarra flame tree flowers reported moderate antimicrobial activity against Bacillus cereus [6] whereas, the antioxidant activity from the leaves showed high activity (IC 50 : 0.015 mg/mL) compared to Vitamin C as a positive control. [7] Despite these reports, there is no information available on the chemical structures contained within this extract.…”
mentioning
confidence: 99%
“…[5] A cursory study of the methanol extract from the Illawarra flame tree flowers reported moderate antimicrobial activity against Bacillus cereus [6] whereas, the antioxidant activity from the leaves showed high activity (IC 50 : 0.015 mg/mL) compared to Vitamin C as a positive control. [7] Despite these reports, there is no information available on the chemical structures contained within this extract.…”
mentioning
confidence: 99%
“…These values were in Please do not adjust margins Please do not adjust margins the same range as those obtained for the corresponding monomers in solution: 340, 320, and 322 nm for coumaric, ferulic, and sinapic acid, respectively. 34,35 However, a slight shift was observed in the maximum absorbance values. This has already been identified as a consequence of the grafting reaction.…”
Section: Grafting Of Lignin Monomers Onto Chitosanmentioning
confidence: 95%
“…[110] Different Sterculia and Brachychiton species were previously known to produce gummy exudates from tree bark which were used since ancient times as stabilizers, emulsifiers and thickeners in food industry and drug-delivery systems. [111][112][113] Gum karaya, obtained from the stem and branches of S. urens, was known 100 years ago as an S. colorata B. acerifolius [10,98] S. colorata B. diversifolius B. diversifolius Farrerol (77) S. urens [90] Puerarin (78) S. foetida [132] alternative to gum tragacanth due to their physical and chemical similarity. Gums can be obtained from other species of Sterculia such as S. setigera and S. villosa in which the gum is collected in India after making incisions or wounds in the tree, and then allowed to solidify to form irregular tears that are consequently cleaned and sorted.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%
“…[96] Anthocyanins and coumarins Sterculia foetida, S. parviflora and B. acerifolius were the major sources of anthocyanins isolated from the genus such as cyanidin, pelargonidin and leucoanthocyanidin glycosides (86)(87)(88)(89)(90)(91)(92)(93). [97][98][99][100] Regarding coumarins, different structures were identified such as scopoletin (94) which was isolated from S. foetida, S. urens and B. australis (S. trichosiphon). [8,90,97] Other coumarins such as scopolin (95) …”
Section: Phenolic Acids and Phenylpropanoidsmentioning
confidence: 99%